A failure criterion for RC members under triaxial compression - Koksal, Hasan Orhun (TECHNO-PRESS, 2006)
The reliable pushover analysis of RC structures requires a realistic prediction of moment-curvature relations, which can be obtained by utilizing proper constitutive models for the stress-strain relationships of laterally confined concrete members. Theoretical approach of Mander is still a single stress-strain model, which employs a multiaxial failure surface for the determination of the ultimate strength of confined concrete. Alternatively, this paper introduces a simple and practical failure criterion for confined concrete with emphasis on introduction of significant modifications into the two-parameter Drucker-Prager model. The new criterion is only applicable to triaxial compression stress state which is exactly the case in the RC columns. Unlike many existing multi-parameter criteria proposed for the concrete fracture, the model needs only the compressive strength of concrete as an independent parameter and also implies for the influence of the Lode angle on the material strength. Adopting Saenz equation for stress-strain plots, satisfactory agreement between the measured and predicted results for the available experimental test data of confined normal and high strength concrete specimens is obtained. Moreover, it is found that further work involving the confinement pressure is still encouraging since the confinement model of Mander overestimates the ultimate strength of some RC columns.
Keywords: failure criterion; compressive strength; concrete; column; stress-strain relation; STRESS-STRAIN BEHAVIOR; CONFINED CONCRETE; STRENGTH; COLUMNS; DUCTILITY; MODEL; Engineering